Exploring the Relationship Between Effective Communication and Employee Participation at NIMASA - Abu, Judith Abu (African Journal of Stability and Development (AJSD), 2025)
This study examined the relationship between effective communication and employee participation within the Nigerian Maritime Administration and Safety Agency (NIMASA). The background highlighted the significance of communication in fostering a participatory workplace culture, thereby addressing the problem of insufficient employee engagement in public organisations. The research was framed within the context of Social Exchange Theory and Organisational Communication Theory, which underscored the importance of clear communication and its impact on employee involvement. Employing a qualitative research design, the study utilised secondary data, interviews, and focus group discussions to gather rich insights from employees across various departments at NIMASA. The findings revealed that clear and open communication channels significantly enhanced employee engagement, job satisfaction, and overall organisational performance. Employees reported feeling more valued and involved when communication was effective, which led to a greater willingness to participate in decision-making processes. The study concluded that effective communication is essential in promoting employee participation and fostering a participatory workplace culture. By addressing barriers to communication, such as unclear messaging and insufficient feedback mechanisms, NIMASA could cultivate an environment that encourages transparency and inclusivity. These findings emphasised the necessity of prioritising communication strategies to enhance employee participation, contributing to the overall success of NIMASA and the broader maritime industry. The research provided actionable recommendations for improving communication and enhancing employee participation, which could serve as a foundation for future studies in similar contexts.